The Effect Of Football Training With Life Skill Content On The Elements Of The Pancasila Student Profile (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of soccer training with life skills content on improving the Pancasila Student Profile elements in students of SMP Negeri 7 Jambi City. The Pancasila Student Profile elements that are the focus of the study include independence, critical thinking, and creativity. This study used a quantitative method with a One Group Pretest-Posttest design. The research sample consisted of 20 students taken through a total sampling technique. The data collection instrument used a validated Likert scale questionnaire. The results showed an increase in the average score on all three elements after being given treatment. For the independence element, the average pretest score was 28.95, increasing to 37.85 in the posttest. For the critical thinking element, the average pretest score was 27.05, increasing to 34.90 in the posttest. Meanwhile, for the creativity element, the average pretest score was 25.80, increasing to 29.35 in the posttest. The results of the paired sample t-test showed a significance value of p < 0.05 for each variable, indicating a significant effect of life skills-based soccer training on improving students' independence, critical thinking, and creativity. Therefore, it can be concluded that soccer training integrated with life skills development is effective in supporting the strengthening of the Pancasila Student Profile elements in students.